Modification of gelatin from tuna skins by green tea polyphenols - Chau Thanh Hien; Dang Minh Nhat; Mac Thi Ha Thanh (Vietnam Journal of Science and Technology, 2023)
This paper presents the result of study on the effect of modifying conditions on properties and structure of tuna skin gelatin by using green tea polyphenols. The results showed that gelatin modified by green tea polyphenols changed its gel strength, degree of cross-linking, molecular weight and gel structure. The appropriate parameters to modify gelatin by using green tea polyphenols which indicated the best mechanical properties were determined as follows: temperature of 40oC in 40 minutes, polyphenol content of 20 mg/g gelatin and gelatin solution of 20%. As a result, modified gelatin showed a decrease in solubility, an increase in cross-linking degree (16.7%), molecular weight (55÷72 kDa) as well as a larger protein structure in comparison with the natural gelatin. The IR spectrograph of the modified gelatin did not show any evidence of forming new functional groups, only an apparent change in the absorption of infrared spectroscopy at the peak of the amide B region was found. The dried modified gelatin became insoluble in hot water.